(untitled) (International Journal of Environmental Sciences, 2025)
Climate change destructive impact on many sectors. One of these is the economic stability, a lifestyle change and transformation economic, political, social and cultural trigger friday as derived from the emission of greenhouse gases in the earth. People have a tendency to a consumption more than usual if threatened in a temperature of hot, hungry and thirsty and desire for comfortable, drive a car, or using air conditioning. Accounting carbon footprint to be that important to observed as early as a sign of sensitivity to the issue of climate change are now global issues. The carbon footprint of the gap in Indonesia existing still use reference The ESDM ministry in 2016, only focused on primary just carbon footprint. Thus there is an important reason measuring accounting carbon footprint with reference scale an international unit version of the latest Climate Steward 2022. The purpose of this research to test the relationship between the costs and emissions. The methodology is survey, by spreading the questionnaire to academics from the polytechnic of Accounting Pontianak based on carbon footprint calculator. It contains a carbon footprint calculator individuals households, vehicles, public transportation, eat and drink and other expenditure that raises the cost of emissions. Population were 1.573 person academica who is a lecturer, tendik, and college students. Engineering the sample collection of clusters of random samples, divided into 4 cluster with a total sample 120 people chosen randomly. Data then tested with the correlation Pearson. The research results show there is a positive correlation between the costs and emissions by value ** 0,806 Pearson indicator. The total cost of the activity of individual academics in Indonesian Rupiah is Rp. 57.289.150 per week with the total emissions of 80.824 kgCO2 per week , it means academics from release 80.824 kilograms of carbon dioxide into the air every weeks. These emissions find that women are the most costs and high yield of emissions. Costs and emissions was the largest by household activity. That is the high cost hence posed to the higher emissions. Accounting carbon footprint and the importance of sensitivity to the environment of the cost we push out. That should be provided by managing green issues.